Anticancer effects of licochalcones: A review of the mechanisms - Deng, Nan; Qiao, Mingming; Li, Ying; Liang, Fengyan; Li, Jingjing; Liu, Yanfeng (Frontiers in Pharmacology, 2023)
Cancer is a disease with a high fatality rate representing a serious threat to human health. Researchers have tried to identify effective anticancer drugs. Licorice is a widely used traditional Chinese medicine with various pharmacological properties, and licorice-derived flavonoids include licochalcones like licochalcone A, licochalcone B, licochalcone C, licochalcone D, licochalcone E, and licochalcone H. By regulating the expression in multiple signaling pathways such as the EGFR/ERK, PI3K/Akt/mTOR, p38/JNK, JAK2/STAT3, MEK/ERK, Wnt/β-catenin, and MKK4/JNK pathways, and their downstream proteins, licochalcones can activate the mitochondrial apoptosis pathway and death receptor pathway, promote autophagy-related protein expression, inhibit the expression of cell cycle proteins and angiogenesis factors, regulate autophagy and apoptosis, and inhibit the proliferation, migration, and invasion of cancer cells. Among the licochalcones, the largest number of studies examined licochalcone A, far more than other licochalcones. Licochalcone A not only has prominent anticancer effects but also can be used to inhibit the efflux of antineoplastic drugs from cancer cells. Moreover, derivatives of licochalcone A exhibit strong antitumor effects. Currently, most results of the anticancer effects of licochalcones are derived from cell experiments. Thus, more clinical studies are needed to confirm the antineoplastic effects of licochalcones.